Acute Respiratory Infection by Chlamydophila pneumoniae and Mycoplasma pneumoniae in a Population of Older Adults in Colombia - Cubides, Nidi Lorena Corredor (2017)
AbstractIntroduction: Acute Respiratory Infection (ARI) is a heterogeneous group of viral and bacterial respiratory pathologies including Chlamydophila pneumoniae (CP) and Mycoplasma pneumoniae (MP) that are not routinely identified; these infections in the older adults have mortality rates 3 to 5 times higher than that recorded in other age groups. Methods: this study was conducted prospectively to determine the proportion of atypical bacterial pathogens in older adults with ARI in Bogotá. Microbiological diagnosis was determined by real-time PCR (qPCR) in samples of respiratory origin and serology for antibodies IgG, IgA and IgM to MP and CP. Results: A total of 71 patients were enrolled from 2012 to 2013. Upper respiratory infections were diagnosed in the 69% of patients and lower respiratory infections in 31%. MP was identified in 9.8% and CP in 8.5%. Conclusions: these findings indicated that CP and MP must be viewed as a significant etiological agent of ARI in older adults in Bogotá.